METAYOLIVERSE : STRATEGI UNTUK MEMPROMOSIKAN UMKM MELALUI ROBLOX - Istiawan, Gregorius Guardiola; Widyasari, Widyasari (Universitas Mercu Buana, 2023)
The industrial world is increasingly modern with the existence of the virtual metaverse world. This can be seen from the existence of the MSIB program on metaverse implemented by CIAS with the